CONTEXTUALISING THE EXPERIENCES OF SOUTH AFRICAN WOMEN IN THE IMMEDIATE AFTERMATH OF RAPE - Womersley, Gail; Maw, Anastasia (PINS-Psychology in Society, 2025)
The psychological impact of rape is most commonly described by drawing on a medical/ psychiatric framework, which feminists have argued fails to factor in the broader contexts of patriarchy and female oppression. Internationally, and in South Africa, feminist researchers have called for more research on rape trauma which seeks to understand the impact of rape in light of the marginalised and oppressive contexts within which particular groups of women live. In response to this need, this article presents a feminist discourse analysis of conversations with nine women living in a low-income area of Cape Town interviewed within 72 hours of being raped. The analysis revealed that the women’s narratives of rape were informed by patriarchal discourses which operated to reinforce gendered relations of power. The discourses discussed in the paper are identified as discourses of damage, ostracism, resistance and survival, confessional discourses and discourses of masculinity and femininity. A multitude of cultural scripts informed the discourses drawn upon by the participants, highlighting the heterogeneous, fluid and dynamic nature of the participants’ subjectivities and indicating that their relation to such discourses are far from being fixed, stable and unambiguous. Furthermore, the dominant discourses highlighted in the findings are understood to play a binding role in maintaining social structures of power.